2022
DOI: 10.1371/journal.pone.0279251
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between religiosity and meaningful work among Malaysian Muslim employees: The mediating role of existential labor

Abstract: This study aimed to explore how religiosity affects the level of meaningful work among Malaysian Muslims, owing to Malaysia’s highly religious background. Although religiosity constitutes a major part of an individual’s value system, the influence of religiosity on the meaningfulness of work remains unclear. To address this gap, this study examined the indirect effects of the two types of religiosity—intrinsic religiosity (IR) and extrinsic religiosity (ER)—on meaningful work through existential labor, namely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…(2020) concluded that the negative influence of job on emotional exhaustion weakens when religion level is higher. Seo et al. (2022) reported that religiosity facilitates employees’ self-regulation, which will boost their long-term benefit.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) concluded that the negative influence of job on emotional exhaustion weakens when religion level is higher. Seo et al. (2022) reported that religiosity facilitates employees’ self-regulation, which will boost their long-term benefit.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(2020) concluded that the negative influence of job on emotional exhaustion weakens when religion level is higher. Seo et al (2022) reported that religiosity facilitates employees' self-regulation, which will boost their long-term benefit. Translated into our context, when confronted to discrimination, employees can resort to their religiosity to mitigate emotional exhaustion.…”
Section: Religiositymentioning
confidence: 99%